2019
DOI: 10.1039/c8tc05476b
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar luminescent azaindole derivative exhibiting aggregation-induced emission for non-doped organic light-emitting diodes

Abstract: A new D–A bipolar luminescent azaindole demonstrates its potential applicability in non-doped OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In consequence, the CB and VB potential levels of TiO 2 were estimated to be located at À0.58 and 2.76 V, respectively (Equations (2) and ( 3)). Using the positions of the LUMO and HOMO of the sensitizer (previously reported [3]), Fig. 7d proposes a plausible band configuration.…”
Section: Photocatalytic Degradation Of Pharmaceuticals Under Simulate...mentioning
confidence: 70%
See 2 more Smart Citations
“…In consequence, the CB and VB potential levels of TiO 2 were estimated to be located at À0.58 and 2.76 V, respectively (Equations (2) and ( 3)). Using the positions of the LUMO and HOMO of the sensitizer (previously reported [3]), Fig. 7d proposes a plausible band configuration.…”
Section: Photocatalytic Degradation Of Pharmaceuticals Under Simulate...mentioning
confidence: 70%
“…The synthesis of the azaindole derivatives was performed following previous works (see Scheme 1a) [3,23]. The AZA1 compound was synthesized through a nucleophilic substitution reaction in the nitrogen position of 5-bromo-7-azaindole with 1iodododecane, KOH, and (Bu) 4 N(HSO 4 ) in acetone.…”
Section: Synthesis Of Azaindole Derivative (Aza4)mentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, isomeric pyrido[2,3- b ]indolizine derivatives were reported by Voskressensky et al, which provided further insights into the structural diversity of indolizine-based fluorophore . 7-Azaindole, notable for its high biocompatibility, is recognized as a weakly fluorescent bioisostere of indole, whereas indolizine has been used in a well-defined fluorophore, Seoul-Fluor, and extensively studied in the structure–photophysical property relationship. Time-dependent density-functional theory (TD-DFT) calculations suggested that pyrido[3,2- b ]indolizine would absorb light nearly in the visible range (396 nm), longer than its original components, 7-azaindole (263 nm) or indolizine (334 nm), despite its compact size.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, C-arylated 7-azaindoles have exhibited desirable applications in organic light-emitting molecules and sensors (Figure ). Propeller-like organic frameworks having peripheral phenyl/aryl groups with different electronic characteristics show aggregation-induced emission (AIE) phenomena attracting material chemists all over the globe . In view of the above, it remains imperative to explore the synthesis of multi-aryl 7-azaindole derivatives for applications in medicinal and material sciences.…”
Section: Introductionmentioning
confidence: 99%